A Randomized, Triple-Blind, Placebo-Controlled Clinical Trial Investigating Two Dietary Supplements on Supporting Immune Function in Healthy Adults in a Flu Vaccine Model. (14th June 2022) - Lewis, Erin; Crowley, David; Guthrie, Najla; Evans, Malkanthi
Abstract: Objectives: To examine the role of two dietary supplements, UP360 and UP446, on supporting immune function in response to influenza vaccination. The ingredients in UP360 and UP446 have been shown to activate the immune system, reduce inflammation and oxidative stress and protect against lung damage. The primary outcome assessed changes in blood lymphocytes (CD3+, CD4+, CD8+, CD45+, TCRγδ+, CD3-CD16 + 56+) and immunoglobulins (IgG, IgM, IgA) between UP360 or UP446 vs. placebo. Methods: This randomized, triple-blind, placebo-controlled, parallel study consisted of a 56-day intervention period with a 28-day pre-vaccination period, influenza vaccination on Day 28 and 28-day post-vaccination period. At baseline, Day 28 and 56, lymphocyte populations, Igs, cytokines, oxidative stress markers and influenza-specific Igs were measured in blood, and a quality of life (QoL) questionnaire was completed. The WURSS-24 was completed daily to assess upper respiratory tract infections (URTIs). Participants were healthy men and women ages 40–80 who had not received their flu vaccine and were willing to maintain their lifestyle habits during the study. Results: In the post-vaccination period, supplementation with UP360 increased the percentage of TCRγδ+ cells compared to placebo (p < 0.001). Total IgA and IgG levels were increased with UP446 supplementation vs. placebo (p ≤ 0.023). UP360 and UP446 groups had increases of 15.6% and 19.4%, respectively, in influenza B-specific IgG in the post-vaccination period (p ≤ 0.0006). Serum glutathione peroxidase (GSH-Px) was increased in the pre-vaccination period in both UP360 and UP446 groups (p ≤ 0.0270). Despite these changes in immune and antioxidant markers, there were no between-group differences in severity, frequency, or duration of URTI symptoms or QoL. Conclusions: These results suggest supplementation with UP360 or UP446 was beneficial in mounting a robust humoral response following vaccination. Increasing GSH-Px in the pre-vaccination period may be beneficial in mitigating the oxidative stress over and above that induced following influenza vaccination and/or viral infection. There were no changes in subjective measures of URTI illness or QoL, demonstrating QoL of these participants was not negatively impacted by supplementation. Funding Sources: Unigen Inc.